LIMINALITAS DALAM RITUAL HAHI DI DESA HULALIU KABUPATEN MALUKU TENGAH: ANALISIS SOSIOLOGI BUDAYA VICTOR TURNER - Maxsi Tupamahu; Cristophel Van Harling (Yayasan Literasi Sains Indonesia, 2025)
The Hahi dance ritual of the Hulaliu indigenous community in Haruku Island, Central Maluku, is a collective rite rich in bodily, spatial, and spiritual symbolism. This study aims to analyze the structure of the Hahi ritual through Victor Turner’s theory of liminality and to explore how ritual symbolism shapes and reinforces social identity and soa-based structures. Using a qualitative approach with content analysis, data were collected through literature review and in-depth interviews with traditional figures. The findings reveal that the Hahi ritual consists of three stages—pre-liminal, liminal, and post-liminal—conducted collectively by the entire community. The liminal stage creates a sense of communitas by temporarily dissolving social hierarchies, thus reinforcing solidarity and ancestral values. Symbols such as body movement, tifa rhythm, ceremonial colors, and sacred spaces like Baileo function as complex mediums of spiritual and social communication. This study concludes that Hahi represents a cyclical and communal liminal experience, serving not only as cultural preservation but also as a form of resistance against modern pressures. It is best understood as a rite of intensification that regenerates social order and sustains collective memory within the indigenous context.